A new current-controlled multiple-output current-conveyor - Abuelma’atti, M.T. (1997)
A new second-generation multiple-output current-controlled current-conveyor (MOCCCC) is presented. It has current-transfer ratios that can be varied by control currents. It is characterized by approximately constant bandwidth over a wide range of current-transfer ratios. The MOCCCC is then used as a building block for realizing electronically-tunable second-order bandpass/lowpass filters. Spice simulation results are presented